Mechanisms for ensuring the security of channels of a prospective management system - Tomashevsky, Bogdan; Yevseiev, S. P.; Pohasii, Serhii; Milevskyi, Stanislav (Національний технічний університет "Харківський політехнічний інститут", 2022)
The development of military (state) control systems in modern conditions of hybrid warfare requires the possibility of rapid expansion of both functionality and scaling of the physical and logical basis of management, increasing the range of digitization and use of both military and civilian communication channels to manage troops and weapons. Not only the computing power of the enemy, the means of suppressing and / or blocking the communication channels of the control system, but also the development of quantum technologies that place new and more stringent requirements on security mechanisms based on symmetric and asymmetric cryptography algorithms. According to NIST, a full-scale quantum computer breaks both symmetric and asymmetric cryptosystems in polynomial time, significantly reducing their resilience. The paper proposes mechanisms of post-quantum cryptography, which allow to ensure the stability of not only communication channels, but also elements of the structure of the control system. The basis of post-quantum encryption algorithms is the combination of algorithms (schemes) of crypto-code structures with cryptosystems on unprofitable codes (multi-channel cryptography), as well as the possibility of combining them with digital steganography methods. This approach provides the ability to hide elements of management commands, and the use of different channels provides the ability to hide individual elements of cryptograms.

Розвиток систем військового (державного) управління в сучасних умовах гібридної війни вимагає можливості стрімкого розширювання як функціональності, так і масштабування фізичної та логічної основи управління, нарощування спектра цифровізації та використання як військових, так і цивільних каналів зв’язку щодо управління військами та зброєю. При цьому необхідно враховувати не тільки обчислювальні можливості противника, засоби придушення та/або блокування каналів зв’язку системи управління, а також розвиток квантових технологій, які висувають нові більш жорсткі вимоги до механізмів забезпечення безпеки на основі алгоритмів симетричної та несиметричної криптографії. За рахунками спеціалістів НІСТ США повномасштабний квантовий комп’ютер забезпечує злам, як симетричних, так й несиметричних криптосистем за поліноміальний час, що суттєво зменшує їх стійкість. В роботі пропонуються механізми постквантової криптографії, які дозволяють забезпечити стійкість не тільки каналів зв’язку, та й елементів структури системи управління. Основою постквантових алгоритмів шифрування поєднання алгоритмів (схем) крипто-кодових конструкцій з криптосистемами на збиткових кодах (багатоканальної криптографії), а також можливість їх поєднання з методами цифровій стеганографії. Такий підхід забезпечує можливість приховування елементів управлінських команд, а використання різних каналів забезпечує можливість приховування окремих елементів криптограм.
Механізми забезпечення безпеки каналів перспективної системи управління
Keywords: crypto-code constructions; algebraic geometric codes4 LDPC-codes; troop control system; quantum period; крипто-кодові конструкції; алгеброгеометричні коди; LDPC-коди; система управління військами; квантовий період